Comparación de implementación CAD vs BIM para proyectos de construcción, arquitectura e ingeniería. - Garcia Coral, Johan Sebastian
This article aimed compare two alternatives for the conceptua- lization of engineering, architectural and construction projects, the first analysis was carried out using Building Information Modeling (BIM), modeling a 5-story multifamily project called Suite 30, establishing a general methodology using tools as Autodesk Revit software, Navisworks and collaborative work tools that allow obtaining the work schedule and budget, this building was modeled in Revit, where the quantities of materials, collisions and the budget for this case were compared; in addition to the time used for its design in the 5 stages where it was developed (research, design, calculation of quantities, time and budget), compared to the review of the bibliographic review of projects that have used the traditional method of Computer Aided Design (CAD) through AutoCad software. As a result of BIM modeling, the project is valued at approximately three billion pe- sos (COP), obtaining a total of 296 collisions, estimating a saving of 1% of collisions ($ 31.222.679) on the total cost, for a modeling time of 5 m2/h, concluding that BIM technology is easier and more efficient to manage, streamlining all design processes.